Check list of the marine commercial and reef fishes of Belitung Timur, Bangka Belitung Islands, Indonesia - Helmy Akbar; Jailani Jailani; Iwan Suyatna; Destilawaty Destilawaty; Singgih Afifa Putra; Indra Ambalika (Syiah Kuala University, 2018)
Marine fish community is very sensitive to environmental changes. So the number of species, abundance, and biodiversity index can be used as a reference to assess the quality of the aquatic environment. The aim of this study was to describe fish biodiversity in Belitung Timur, Bangka Belitung Islands, Indonesia. Three islands were visited i.e. Pekandis Island, and Keran Island, Gosong Semut (Gosong refers to sandbar) for reef fish survey and for the economical fish study we also visited fisheries landing sites (i.e. Teluk Pering, Tanjung Batu Pulas, and Pantai Burung Mandi). The underwater visual census was used for in situ surveys of reef fish, and the fish species landed in fisheries landing site also been checked. Forty-two families of economical fish that had been landed by local fishermen were identified, and ten families of reef fish were found in reef systems of research location. A total of 10 families were recorded from three islands in Belitung Timur Regency. In addition, 42 families of commercial fish were also observed in fish landing sites from the coastline of Belitung Timur Regency, Bangka Belitung Islands.